Twenty-four hour and spot urine metabolic evaluations: correlations versus agreements - Hong, Y.H.; Dublin, N.; Razack, A.H.; Mohd, M.A.; Husain, R. (2010)
OBJECTIVES To investigate the correlations and agreements between the solute/creatinine ratios from the 24-hour and early morning spot urine samples for metabolic evaluation in stone-formers given the various pitfalls with the 24-hour urinary metabolic evaluation in stone-formers. METHODS 30 urinary stone-formers out of an initial 62 recruited provided a complete 24-hour urine and early morning spot urine samples for metabolic evaluation. Pearson correlation and Bland and Altman Test were used to assess the correlations and agreements. RESULTS Significant correlations were established between the 24-hour urinary solute excretions and the corresponding early morning spot urine solute/creatinine ratios for calcium, magnesium, urate, potassium, oxalate, citrate, and the Differential Gibb's free energy value of calcium oxalate DG(CaOx) values. However, all these solute/creatinine measurements between the 24-hour and early morning spot urine samples were judged to be not within the acceptable limits based on the estimated "limit of agreement" by the Bland and Altman Test of Agreement. Diurnal circadian rhythm and postprandial excretion surge are thought to be responsible for the disagreements. CONCLUSIONS Thus, the early morning spot urine is not suitable to be used interchangeably to replace the 24-hour urine collection in the evaluation of urinary metabolic abnormalities in stone-formers. A good correlation does not translate to an agreement between the 2 measurements. UROLOGY 75: 1294-1298, 2010. (C) 2010 Elsevier Inc.